Packaging material and manufacturing method thereof

JP2025036127AInactive Publication Date: 2025-03-14TOYO INK MFG CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2024111058
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-07-10
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0017】 本発明により、リリース性、ヒートシール性、耐突き刺し性、及び折り曲げ後の水蒸気バリア性が良好な包装材を提供する。更には、耐水摩擦性、耐熱性に優れた包装材を提供することが可能となった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036127000001
    Figure 2025036127000001
  • Figure 2025036127000002
    Figure 2025036127000002
  • Figure 2025036127000003
    Figure 2025036127000003
Patent Text Reader

Abstract

To provide a packaging material having excellent water-proof abrasion resistance, heat resistance, releasing property, heat sealing property and puncture resistance.SOLUTION: There is provided a packaging material having a heat seal layer, a barrier layer, a paper base material, a printing layer and a surface protective layer, wherein the surface protective layer contains a styrene-acrylic copolymer resin (A), the printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, the barrier layer contains at least one selected from the group consisting of a polyvinyl alcohol-based resin, a styrene-based resin (C), an acrylic-based resin (D'), aluminum, and an inorganic oxide, and a 60 degree gloss value of the surface protective layer measured by the method described in JIS Z 8741:1997 is 10 to 45.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging material and a method for producing the same. [Background technology]

[0002] In recent years, it has become common for product packages and other wrapping materials to be printed for decoration and surface protection. Furthermore, the quality of printing, such as the design, beauty, and luxury of the printed matter, can stimulate consumer purchasing motivation and is of great industrial value.

[0003] Generally, plastic films are mainly used to construct packages, and laminated packaging materials are often used in particular. For example, Patent Document 1 describes an invention of a laminated packaging material consisting of a base material, a printing layer, an adhesive layer, and a sealant layer, in which biomass resin is used in the printing layer and the adhesive layer. However, laminated packaging materials originally use a large amount of plastic film made of petroleum-derived materials. Therefore, there is a demand for paper-based packaging materials that are environmentally friendly, carbon neutral, and can further reduce the amount of plastic used, and technological developments are being made.

[0004] For example, as an example of using a paper substrate as part of a packaging material, Patent Document 2 describes an invention relating to a paper laminate having, in order, a resin layer, a print layer, a paper substrate layer, a metal deposition film layer, a gas barrier coating layer, and a heat-sealable resin layer. However, the resin layer is formed of low-density polyethylene or the like with a low glass transition temperature in order to provide heat sealability, and the toughness of the coating is insufficient, leaving problems with the releasability and heat resistance of the packaging material.

[0005] For example, Patent Document 3 describes an invention relating to a packaging material having a surface protective layer, a printing layer, a paper substrate layer, and a resin layer in that order, and the surface protective layer contains nitrocellulose. However, since the surface protective layer is formed only from nitrocellulose, it lacks water resistance and toughness, and therefore there are problems with the releasability and puncture resistance of the packaging material.

[0006] Therefore, there is a demand for packaging materials that do not use a large amount of plastic, such as laminate packaging materials, and for example, packaging materials using a paper base material are desired, but a satisfactory packaging material with excellent releasability and puncture resistance has not yet been found. Therefore, in order to impart practicality to packaging materials using a paper base material, in addition to solving the above problems, it is necessary to improve the water friction resistance, heat resistance, and heat sealability required of packaging materials. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2018-051796 A [Patent Document 2] JP 2006-256198 A [Patent Document 3] JP 2020-55171 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention provides a packaging material having good releasability, heat sealability, puncture resistance, and water vapor barrier property after folding. Another object of the present invention is to provide a packaging material having excellent water friction resistance and heat resistance. [Means for solving the problem]

[0009] As a result of extensive research into the above problems, the present inventors have found that the above problems can be solved by using the packaging material described below, and have thus completed the present invention.

[0010] That is, the present invention provides a packaging material having a heat seal layer, a barrier layer, a paper base material, a printing layer, and a surface protective layer, the surface protective layer comprises a styrene-acrylic copolymer resin (A), The printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, the barrier layer comprises at least one selected from the group consisting of a polyvinyl alcohol-based resin, a styrene-based resin (C), an acrylic-based resin (D'), aluminum, and an inorganic oxide; The surface protective layer was measured by the method described in JIS Z8741:1997. The present invention relates to a packaging material having a 60 degree gloss value of 10 to 45.

[0011] That is, the present invention relates to the packaging material, wherein the surface protective layer has a 60 degree gloss value of 10 to 35, as measured by the method described in JIS Z8741:1997.

[0012] That is, the present invention relates to the packaging material, wherein the heat seal layer has a thickness of 1 to 10 μm.

[0013] That is, the present invention is a method for producing a paper substrate having an average basis weight of 50 to 300 g / m 2 The present invention relates to the packaging material,

[0014] That is, the present invention relates to the packaging material, wherein the heat seal layer contains at least one member selected from the group consisting of ethylene-vinyl acetate copolymer resins, acrylic resins (D), and ethylene-based ionomers.

[0015] That is, the present invention relates to a packaging bag formed from the packaging material.

[0016] That is, the present invention is a method for producing a packaging material having a heat seal layer, a barrier layer, a paper base material, a printing layer, and a surface protective layer, comprising the steps of: A step 1 of forming the printing layer by flexographically printing a printing ink containing a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin on one surface of the substrate containing the paper substrate; An overcoat agent containing a styrene-acrylic copolymer resin (A) is applied onto the printed layer by flexographic printing. The 60 degree gloss of the surface protective layer was measured using the method described in JIS Z 8741:1997. A step 2 of forming a surface protective layer having a viscosity value of 10 to 45; Step 3 of applying a heat seal agent to the other surface of the base material including the paper base material to form a heat seal layer; and step 4 of forming a barrier layer containing at least one selected from the group consisting of a polyvinyl alcohol-based resin, a styrene-based resin (C), an acrylic-based resin (D'), aluminum, and an inorganic oxide on the substrate containing the paper substrate. Effect of the Invention

[0017] The present invention provides a packaging material having good releasability, heat sealability, puncture resistance, and water vapor barrier property after folding. It is also possible to provide a packaging material having excellent water, friction, and heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The following describes in detail the embodiments of the present invention. However, the following description of the components is merely an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0019] In the following description, unless otherwise specified, "parts" refers to "parts by mass" and "%" refers to "% by mass." In addition, the packaging material may be abbreviated simply as "laminate," but this has the same meaning. In the following description of the present invention, "printing ink" refers to ink containing pigments and other colorants for forming a printed layer, and "overcoat agent" refers to a coating agent for forming a surface protective layer that does not contain pigments or other colorants, but does not exclude traces of colorants that have been unintentionally mixed in.

[0020] [Packaging material] The present invention relates to a packaging material having a heat seal layer, a barrier layer, a paper substrate, a printing layer, and a surface protective layer, the surface protective layer containing a styrene-acrylic copolymer resin (A), the printing layer containing a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, the barrier layer containing at least one selected from the group consisting of a polyvinyl alcohol resin, a styrene-based resin (C), an acrylic resin (D), aluminum, and an inorganic oxide, and the surface protective layer has a 60 degree gloss value of 10 to 40 measured by the method described in JIS Z8741:1997. This configuration improves heat sealability and releasability, and the inclusion of the styrene-acrylic copolymer resin (A) in the surface protective layer improves heat resistance, puncture resistance, water abrasion resistance, and water vapor barrier property after folding. The packaging material of the present invention has a barrier layer, a printing layer, and a surface protective layer containing the above materials, and thus the amount of light penetrating into the entire packaging material can be controlled, and the above gloss value can be achieved. The packaging material of the present invention may further include an adhesive resin layer for bonding the barrier layer and the paper base layer. Furthermore, the packaging material of the present invention may further include an anchor coat layer.

[0021] Suitable examples of the layered structure of the packaging material are as follows: In the following examples, " / " indicates the boundary between layers. Heat seal layer / barrier layer / paper base layer / printing layer / surface protection layer Heat seal layer / paper base layer / barrier layer / printing layer / surface protection layer Heat seal layer / paper base layer / printing layer / barrier layer / surface protection layer Heat seal layer / anchor coat layer / barrier layer / paper base layer / printing layer / surface protection layer Heat seal layer / anchor coat layer / paper base layer / barrier layer / printing layer / surface protection layer Heat seal layer / anchor coat layer / paper base layer / printing layer / barrier layer / surface protection layer Heat seal layer / barrier layer / paper base layer / anchor coat layer / printing layer / surface protection layer Heat seal layer / paper base layer / anchor coat layer / barrier layer / printing layer / surface protection layer Heat seal layer / paper base layer / anchor coat layer / printing layer / barrier layer / surface protection layer Among these, it is more preferable to have a heat seal layer, a barrier layer, a paper base layer, a printing layer, and a surface protection layer in this order.

[0022] [Surface protective layer] The surface protective layer contains a styrene-acrylic copolymer resin (A). In the surface protective layer, the content of the styrene-acrylic copolymer resin (A) is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the solid content of the surface protective layer. When the content of the styrene-acrylic copolymer resin (A) is within the above range, the toughness of the surface protective layer is increased, and the heat resistance of the packaging material is improved. In addition, the thickness of the surface protective layer is preferably 0.3 to 10 μm, more preferably 1 to 7 μm, and even more preferably 3 to 5 μm.

[0023] The gloss value of the surface protective layer is from 10 to 45, more preferably from 10 to 40, still more preferably from 10 to 35, and particularly preferably from 10 to 20. The above gloss value is a 60 degree gloss value (Gs(60)) measured in accordance with JIS Z 8741:1997. When the gloss value is within the above range, water friction resistance tends to be improved. The gloss value is different from the gloss (mirror reflection) of a metal layer such as an aluminum vapor deposition layer on the inside of a packaging material.

[0024] <Styrene-acrylic copolymer resin (A) contained in surface protective layer> The styrene-acrylic copolymer resin (A) is preferably an aqueous resin, which may be either a water-soluble resin or an aqueous emulsion resin, but is preferably an aqueous emulsion resin.

[0025] The styrene-acrylic copolymer resin (A) can be obtained by copolymerizing an acrylic monomer and a styrene monomer by a known method, and examples of the constituent styrene monomer include styrene, α-methylstyrene, β-methylstyrene, etc. These may be used alone or in combination of two or more. Among these, the styrene monomer preferably contains α-methylstyrene.

[0026] Suitable examples of the acrylic monomer include acrylic acid esters, methacrylic acid esters, etc. For example, examples of the acrylic acid esters include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethylaminoethyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, and glycidyl acrylate, and examples of the methacrylic acid esters include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, dimethylaminoethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and glycidyl methacrylate. Also usable are carboxylic acid-containing monomers such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, and the anhydrides and half esters thereof. These may be used alone or in combination of two or more.

[0027] The styrene-acrylic copolymer resin (A) preferably has an acid group, and in that case, the acid value is preferably 20 to 200 mgKOH / g, more preferably 30 to 150 mgKOH / g, and further preferably 80 to 120 mgKOH / g. When the styrene-acrylic copolymer resin (A) has an acid group and the acid value is within the above range, the releasability and heat resistance of the packaging material are good.

[0028] The weight average molecular weight of the styrene-acrylic copolymer resin (A) is preferably from 2,000 to 600,000, more preferably from 50,000 to 600,000, and particularly preferably from 70,000 to 600,000.

[0029] The glass transition temperature of the styrene-acrylic copolymer resin (A) is preferably from -20 to 80°C, more preferably from -10 to 60°C, and further preferably from 0 to 40°C.

[0030] When the weight average molecular weight and glass transition temperature of the styrene-acrylic copolymer resin (A) are within the above ranges, it becomes possible to achieve both toughness and flexibility in the printed layer, resulting in good releasability and puncture resistance.

[0031] The acid value is the number of milligrams of potassium hydroxide required to neutralize the acidic groups contained in 1 g of resin solid content, and is measured in accordance with JIS K0070.

[0032] The weight average molecular weight (Mw) can be measured, for example, by GPC (gel permeation chromatography), and can be calculated as a molecular weight converted using polyethylene glycol as a standard substance. The measuring device can be a GPC device such as Shodex GPC-401 manufactured by Showa Denko K.K., and the column can be a Shodex OHpak LB-805 manufactured by Showa Denko K.K., and the detector can be an RI (differential refractometer), and the measurement temperature is preferably a column temperature of 20 to 50°C. The eluent can be an aqueous solution of 0.1N NaNO3, and the flow rate is generally 0.2 to 5.0 mL / min.

[0033] The glass transition temperature can be measured, for example, using a differential scanning calorimeter (DSC measuring device, Shimadzu Corporation's "DSC-60A"), and the temperature of the inflection point in the baseline shift can be used as the glass transition temperature. The measurement is preferably performed in a nitrogen atmosphere, with the measurement temperature range being -100 to 200°C and the heating rate being 1 to 5°C / min.

[0034] The content of the structure derived from a styrene monomer in 100% by mass of the surface protective layer is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20 to 70% by mass.

[0035] <Other resins contained in the surface protective layer> The surface protective layer may further contain other resins. Examples of other resins include urethane resins, polylactic acid resins, polyamide resins, vinyl chloride-acrylic copolymer resins, castor oil resins, rosin resins, vinyl acetate resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, urethane-acrylic resins, styrene-allyl alcohol copolymer resins, styrene-maleic acid copolymer resins, rosin-modified maleic acid resins, dammar resins, and modified resins thereof. These resins can be used alone or in combination of two or more.

[0036] The styrene-acrylic copolymer resin (A) contained in the surface protective layer may be a commercially available product, for example, Joncryl 74J, Joncryl 537E, etc., manufactured by BASF.

[0037] <Additives contained in the surface protective layer> The surface protective layer of the present invention may contain various additives as required, such as dispersants, waxes, extender pigments, leveling agents, defoamers, film-forming assistants, water repellents, and release agents (silicone). Specifically, various additives can be added, such as dispersions of wax resin particles such as polyethylene wax to improve abrasion resistance; extender pigments such as silica, barium sulfate, resin beads, calcium carbonate, and talc to improve drying properties and coating film hiding properties; inorganic particles and adhesive resins (acrylic resin, vinyl acetate resin) to impart anti-slip properties; leveling agents to improve leveling properties; antifoaming agents to impart antifoaming properties; basic compounds such as sodium hydroxide and potassium hydroxide to impart re-solubility; and film-forming aids.

[0038] <Overcoat agent> The surface protective layer is preferably formed by an overcoat agent. The overcoat agent is preferably an aqueous overcoat agent. The overcoat agent preferably contains a styrene-acrylic copolymer resin (A) and an aqueous medium, and may further contain resins and additives other than the styrene-acrylic copolymer resin (A).

[0039] The solid content of the styrene-acrylic copolymer resin (A) in the overcoat agent is preferably 25 to 100 mass %, more preferably 25 to 75 mass %, and particularly preferably 25 to 45 mass %, of the total mass of the overcoat agent.

[0040] (aqueous medium) The overcoat agent preferably contains an aqueous medium. The main component of the aqueous medium is preferably water, but in addition to water, a water-soluble organic solvent can be used. Specifically, depending on the printing conditions (speed, plate depth, design, drying temperature), an alcohol-based organic solvent, a glycol-based organic solvent, etc. can be contained. The content of the aqueous medium is preferably 30% by mass or less based on the total amount of the overcoat agent. In the present invention, the term "mainly water" means that the water content is the largest in the aqueous medium, and the water-soluble organic solvent means a solvent that is liquid at 25° C. and does not undergo phase separation when mixed with water at 25° C. in a 1:1 ratio.

[0041] Examples of the alcohol-based organic solvent include methanol, ethanol, propanol, isopropanol, isobutanol, normal butanol, tertiary butanol, hexanol, octanol, and decanol.

[0042] Examples of the glycol-based organic solvent include ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monooctyl ether, diethylene glycol, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, propylene glycol, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol monopropyl ether, tripropylene glycol monobutyl ether, and dibutyl glycol. These may be used alone or in combination of two or more.

[0043] <Method of manufacturing the overcoat agent> The overcoat agent can be obtained by feeding a resin solution, in which a resin is dissolved or dispersed in an organic solvent, and a solvent into an agitator equipped with an agitating blade, a rotor, etc., and mixing and stirring the solvent. There is no particular restriction on the stirring speed, and stirring can be performed at 50 to 2000 rpm. In order to improve the handling and coating properties of the overcoat agent, a solvent can also be appropriately added. From the viewpoint of printability and the like, the viscosity of the overcoat agent at 25° C. is preferably 50 to 300 mPa·s.

[0044] <Formation of surface protective layer> The surface protective layer can be formed, for example, by printing an overcoat agent on a printed layer of a laminate in which a printed layer is provided on a substrate, and then removing the volatile components. The printing method includes a flexographic printing method, in which, for example, the overcoat agent is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture and applied. Thereafter, the coating is fixed by drying in an oven or the like to obtain a surface protective layer.

[0045] [Print layer] The printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin. The styrene-acrylic copolymer resin (B) may be the same as the above-mentioned styrene-acrylic copolymer resin (A). In the printing layer, the total solid content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is preferably 10 to 70 mass% of the total solid mass of the printing layer, and more preferably 30 to 50 mass%. When the total mass content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is within the above range, it is possible to achieve both toughness and flexibility, and therefore the releasability and puncture resistance are good. The content ratio of the styrene monomer-derived structure in 100 mass% of the printing layer is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 20 to 70 mass%.

[0046] The acid groups of the styrene-acrylic copolymer resin (B) and / or the styrene-maleic acid copolymer resin are preferably neutralized with a basic compound. Examples of the acid groups include hydroxyl groups, aldehyde groups, carbonyl groups, and carboxy groups, and the like, with carboxy groups being preferred. Suitable examples of the basic compounds include amine compounds and alkali metals.

[0047] Examples of the amine compound include ammonia, alkylamines such as diethylamine, triethylamine, and ethylenediamine, and alkanolamines such as monoethanolamine, ethylethanolamine, diethylethanolamine, diethanolamine, and triethanolamine. Examples of the alkali metal include sodium hydroxide and potassium hydroxide. These may be used alone or in combination of two or more.

[0048] The total solid content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is preferably 50 mass% or more, more preferably 70 mass% or more, and particularly preferably 90 mass% or more, of the total solid mass of the resins contained in the printing layer.

[0049] The printing layer preferably contains an aqueous resin. The aqueous resin refers to a resin that can be dissolved or dispersed in water, and includes water-soluble resins and aqueous emulsion resins. Here, the aqueous emulsion resin refers to a resin that is insoluble or poorly soluble in water, but is stabilized in dispersion in water using a surfactant or the like. The aqueous resin may be the above-mentioned styrene-acrylic copolymer resin (B) and / or styrene-maleic acid copolymer resin.

[0050] When the printed layer contains an aqueous emulsion resin, the average particle size of the aqueous emulsion resin is preferably 10 to 500 nm, and more preferably 30 to 200 nm. When a printing ink is used to form the printed layer, the average particle size is the average particle size in the printing ink.

[0051] The printed layer preferably contains both the water-soluble resin and the aqueous emulsion. The solid content ratio of the water-soluble resin and the aqueous emulsion resin is preferably water-soluble resin:aqueous emulsion resin=1:99 to 75:25, more preferably 1:99 to 55:45, and particularly preferably 15:85 to 35:65. At the above ratio, the balance between the water resistance and toughness of the printed layer is good, and the packaging material has good water friction resistance, releasability, and puncture resistance.

[0052] The thickness of the printed layer is preferably 0.1 to 10 μm, more preferably 0.3 to 6 μm, and particularly preferably 0.5 to 3 μm. In the present invention, not only a single printed layer but also a layer in which multiple printed layers are overlapped is regarded as the printed layer, and printed layers with different hues can be arbitrarily combined.

[0053] (Styrene-acrylic copolymer resin (B)) The styrene-acrylic copolymer resin (B) may be a water-soluble styrene-acrylic copolymer resin (b1) used as a water-soluble resin, or a styrene-acrylic copolymer resin emulsion (b2) used as an aqueous emulsion resin.

[0054] (Water-soluble styrene-acrylic copolymer resin (b1)) The water-soluble styrene-acrylic copolymer resin (b1) preferably has an acid group, and in that case, the acid value is preferably 150 to 350 mgKOH / g, more preferably 200 to 300 mgKOH / g. When the water-soluble styrene-acrylic copolymer resin (b1) has an acid group and the acid value is within the above range, the releasability and heat resistance of the packaging material are good.

[0055] The weight average molecular weight of the water-soluble styrene-acrylic copolymer resin (b1) is preferably 1,500 to 50,000, more preferably 1,500 to 30,000, and particularly preferably 1,500 to 8,000.

[0056] The water-soluble styrene-acrylic copolymer resin (b1) has a glass transition temperature of preferably 40 to 130°C, more preferably 60 to 100°C.

[0057] When the weight average molecular weight and glass transition temperature of the water-soluble styrene-acrylic copolymer resin (b1) are within the above ranges, the packaging material has good releasability and puncture resistance.

[0058] The water-soluble styrene-acrylic copolymer resin (b1) may be a commercially available product, for example, GL-2439 or YL-1098 manufactured by Seiko PMC Corporation.

[0059] (Styrene-acrylic copolymer resin emulsion (b2)) The styrene-acrylic copolymer resin emulsion (b2) preferably has an acid group, and in that case, the acid value is preferably 5 to 80 mgKOH / g, more preferably 20 to 60 mgKOH / g. When the styrene-acrylic copolymer resin emulsion (b2) has an acid group and the acid value is within the above range, the water friction resistance and heat resistance of the packaging material are good.

[0060] The weight average molecular weight of the styrene-acrylic copolymer resin emulsion (b2) is preferably 2,000 to 600,000, and more preferably 10,000 to 600,000.

[0061] The glass transition temperature of the styrene-acrylic copolymer resin emulsion (b2) is preferably from -20 to 60°C, more preferably from 0 to 40°C.

[0062] When the weight average molecular weight and glass transition temperature of the styrene-acrylic copolymer resin emulsion (b2) are within the above ranges, the packaging material has good releasability and puncture resistance.

[0063] As the styrene-acrylic copolymer resin emulsion (b2), a commercially available product may be used, and examples thereof include JONCRYL 662, 669, 668, 665, 667, PDX 7198, 633-E, LMV7051, 90, and HPD396 manufactured by BASF.

[0064] (Styrene-maleic acid copolymer resin) The styrene-maleic acid copolymer resin is preferably used as a water-soluble resin. The styrene-maleic acid copolymer resin preferably has an acid group, and in this case, the acid value is preferably 100 to 180 mgKOH / g, and more preferably 120 to 160 mgKOH / g. When the styrene-maleic acid copolymer resin has an acid group and the acid value is within the above range, the water friction resistance and heat resistance of the packaging material are good.

[0065] The weight average molecular weight of the styrene-maleic acid copolymer resin is preferably 1,500 to 50,000, and more preferably 4,000 to 30,000.

[0066] The glass transition temperature of the styrene-maleic acid copolymer resin is preferably from 40 to 120°C, more preferably from 60 to 100°C.

[0067] When the weight average molecular weight and glass transition temperature of the styrene-maleic acid copolymer resin are within the above ranges, the packaging material has good water abrasion resistance and puncture resistance.

[0068] As the styrene-maleic acid copolymer resin, commercially available products may be used, for example, M-30 manufactured by Seiko PMC Corporation and Alastar series manufactured by Arakawa Chemical Industries, Ltd. can be used.

[0069] <Other resins contained in the printing layer> The printing layer may further contain other resins, such as acrylic resins, urethane resins, polylactic acid resins, polyamide resins, vinyl chloride-acrylic copolymer resins, castor oil resins, rosin resins, vinyl acetate resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, styrene-allyl alcohol copolymer resins, rosin-modified maleic acid resins, dammar resins, and modified resins thereof.

[0070] <Colorant contained in the printing layer> The printed layer preferably contains a colorant, and the content of the colorant is preferably 1 to 60% by mass, and more preferably 30 to 50% by mass, based on the total mass of the solid content of the printed layer.

[0071] The colorant is preferably a pigment, and either an organic pigment or an inorganic pigment can be used. As the organic pigment, it is preferable to use a pigment made of an organic compound and / or an organic metal complex. As the inorganic pigment, it is preferable to use one containing titanium oxide.

[0072] Specific examples of organic pigments are shown by their Colour Index International (CI) numbers. Preferably, CI Pigment Red 57:1, CI Pigment Red 48:1, CI Pigment Red 48:2, CI Pigment Red 48:3, CI Pigment Red 146, CI Pigment Red 242, CI Pigment Yellow 83, CI Pigment Yellow 14, CI Pigment Orange 64, CI Pigment Orange 38, CI Pigment Orange 34, CI Pigment Orange 13, CI Pigment Yellow 180, CI Pigment Yellow 139, CI Pigment Red 185, CI Pigment Red 122, CI Pigment Red 178, CI Pigment Red 149, CI Pigment Red 144, CI Pigment Red 166, CI Pigment Violet 23, CI Pigment Violet 37, CI Pigment Blue 15, CI Pigment Blue 15:1, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 15:4, CI Pigment Blue 15:6, CI Pigment Green 7, CI Pigment Orange 34, CI Pigment Orange 64, and CI Pigment Black 7. These may be used alone or in combination of two or more.

[0073] (Inorganic pigments) Examples of inorganic pigments include titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silica, aluminum particles, mica, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, red iron oxide, yellow iron oxide, iron black, titanium oxide, and zinc oxide. Aluminum can be either leafing or non-leafing type, with the non-leafing type being preferred.

[0074] Titanium oxide Titanium oxide may be used in any of the crystal structures of anatase, rutile, and brookite. Among them, rutile titanium oxide is preferred because of its good pigment dispersibility. In industrial production of titanium oxide, rutile ore or ilmenite ore (FeTiO3) is used as the raw material. There are two main manufacturing methods: the chlorine method and the sulfuric acid method, and either method may be used. In addition, in order to improve printability in flexographic printing, it is preferable that the titanium oxide is surface-treated, and in particular, that the titanium oxide is surface-treated with at least one metal selected from the group consisting of Si, Al, Zn, Zr, and oxides thereof.

[0075] The titanium oxide preferably has an oil absorption of 14 to 35 ml / 100 g, more preferably 17 to 32 ml / 100 g, as measured by the method specified in JIS K5101. The titanium oxide preferably has an average particle size (median particle size) of 0.2 to 0.3 μm, as measured by a transmission electron microscope. The total content of the titanium oxide is preferably 1 to 60% by mass, more preferably 10 to 45% by mass, in 100% by mass of the printing ink. Multiple types of titanium oxide may be used in combination.

[0076] <Additives contained in the printing layer> The printing layer of the present invention may contain various additives as required, such as dispersants, waxes, extender pigments, leveling agents, antifoaming agents, and film-forming assistants. Specifically, various additives can be added, such as dispersions of wax resin particles such as polyethylene wax to improve abrasion resistance; extender pigments such as calcium carbonate, kaolin, barium sulfate, aluminum hydroxide, clay, and talc to improve drying properties and coating film hiding properties; inorganic particles and adhesive resins (acrylic resin, vinyl acetate resin) to impart anti-slip properties; leveling agents to improve leveling properties; antifoaming agents to impart antifoaming properties; basic compounds such as sodium hydroxide and potassium hydroxide to impart resolubility; and film-forming aids.

[0077] <Printing ink> The printed layer is preferably formed from a printing ink containing the above-mentioned colorant and the above-mentioned binder resin.

[0078] <Printing ink manufacturing method> The printing ink used to form the printing layer can be produced, for example, by dispersing a pigment in an organic solvent with a resin or the like using a disperser, and mixing the resulting pigment dispersion with a resin, various additives, an organic solvent, and the like. As the disperser, a commonly used one, for example, a roller mill, a ball mill, a pebble mill, an attritor, or a sand mill, can be used. The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the grinding media of the disperser, the filling rate of the grinding media, the dispersion processing time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, and the like. The viscosity of the printing ink at 25°C is preferably in the range of 50 mPa·s or more from the viewpoint of preventing the pigment from settling and dispersing appropriately, and 300 mPa·s or less from the viewpoint of workability efficiency during ink production and printing. For example, the method described in JP-A-2018-158986 can be used as the method for producing the printing ink.

[0079] <Formation of printing layer> The printing layer can be formed, for example, by printing with a printing ink on the paper substrate surface opposite to the heat seal layer, and then removing the volatile components. A suitable printing method is flexographic printing, in which, for example, the ink is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture, and applied. The printing layer can then be obtained by fixing the coating by drying in an oven or the like.

[0080] [Heat seal layer] The heat seal layer in the present invention is located on the paper substrate opposite to the surface having the printing layer. The heat seal layer contains at least one selected from the group consisting of ethylene-vinyl acetate copolymer resin, acrylic resin (D) and ethylene-based ionomer. The resin contained in the heat seal layer may contain urethane resin, polyethylene resin, polypropylene resin, etc. in addition to ethylene-vinyl acetate copolymer resin, acrylic resin and ethylene-based ionomer. These may be used alone or in combination of two or more.

[0081] <Ethylene-vinyl acetate copolymer resin> The ethylene-vinyl acetate copolymer resin is a copolymer made of ethylene and vinyl acetate. The vinyl acetate content in the ethylene-vinyl acetate copolymer resin is preferably 5 to 50 mass%, more preferably 10 to 40 mass%, and particularly preferably 20 to 30 mass%, based on 100 mass% of the ethylene-vinyl acetate copolymer resin. The minimum film-forming temperature of the ethylene-vinyl acetate copolymer resin is preferably 40 to 120°C, more preferably 60 to 100°C. When the vinyl acetate content and the minimum film-forming temperature are within the above ranges, the heat sealability is good. The glass transition temperature of the ethylene-vinyl acetate copolymer resin is preferably -60 to 20°C, more preferably -25 to 5°C.

[0082] Examples of the ethylene-vinyl acetate copolymer resin that can be used include Aquatex EC series manufactured by Japan Coating Resins Co., Ltd. and Sumikaflex S-201HQ, S-305, S-305HQ, S-400HQ, S-401HQ, S-408HQE, S-450HQ, S-455HQ, S-456HQ, S-460HQ, S-467HQ, S-470HQ, S-480HQ, S-510HQ, S-520HQ, S-752, and S-755 manufactured by Sumitomo Chemical Co., Ltd.

[0083] <Acrylic resin (D)> The acrylic resin (D) is a resin containing a structural unit derived from an acrylic monomer. The acrylic resin (D) preferably has a carboxyl group or other acidic group. The acid value of the acrylic resin (D) is preferably 20 to 120 mgKOH / g, more preferably 30 to 100 mgKOH / g, and particularly preferably 40 to 80 mgKOH / g. When the acid value of the acrylic resin (D) is 20 mgKOH / g or more, the recyclability is good, and when it is 120 mgKOH / g or less, the blocking resistance is good. The glass transition temperature of the acrylic resin (D) is preferably -40 to 90°C, more preferably -30 to 70°C, and particularly preferably -20 to 50°C. When the glass transition temperature of the acrylic resin is within the above range, the blocking resistance and heat sealability are good. In addition, the acrylic resin (D) is preferably a homopolymer of an acrylic monomer, a copolymer of an acrylic monomer and an acidic monomer, or a copolymer of ethylene and an acrylic monomer.

[0084] Examples of the monomer having an unsaturated double bond including the (meth)acrylic monomer include alkyl ester compounds of (meth)acrylic acid such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate; (meth)acrylic acid amide derivatives containing at least one N-substituted methylol group, such as N-methylol (meth)acrylamide; Aminoalkyl esters of (meth)acrylic acid such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dipropylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, diethylaminopropyl (meth)acrylate, and dipropylaminopropyl (meth)acrylate; Mono- or diesters of (meth)acrylic acid of glycols such as diethylene glycol and dipropylene glycol, Styrene, α-methylstyrene and other styrene derivatives, Hydroxyalkyl ester compounds of (meth)acrylic acid, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 3-hydroxypropyl (meth)acrylate; Acrylic acid, methacrylic acid, Examples of suitable vinyl compounds include those having an acid group such as maleic acid and itaconic acid. From the viewpoint of heat sealability, the acrylic resin (D) preferably has a carboxyl group and / or a hydroxyl group, and when the acrylic resin (D) has a hydroxyl group, it is preferable that the acrylic resin (D) contains a hydroxyalkyl ester compound of (meth)acrylic acid as a monomer constituting the acrylic resin (D).

[0085] The acrylic resin (D) may be a commercially available product, for example, JONCRYL PDX7356, PDX-7326, PDX-7430 manufactured by BASF, PE-1126, JE-1113, KE1148 manufactured by Seiko PMC Corporation, etc.

[0086] <Ethylene-based ionomer> Ethylene-based ionomer is a general term for resins in which the molecules of copolymers of ethylene and (meth)acrylic acid are intermolecularly bonded by metal ions. For example, metal salts of ethylene-methacrylic acid copolymers, metal salts of ethylene-acrylic copolymers, metal salts of ethylene-urethane copolymers, metal salts of ethylene-fluorine polymers, etc. are all called ethylene-based ionomers. Examples of metal ions that form salts include alkali metal ions and alkaline earth metal ions, specifically, sodium, potassium, calcium, magnesium, and zinc ions. The minimum film-forming temperature of ethylene-based ionomer resins is preferably 20 to 100°C, more preferably 40 to 80°C. When the minimum film-forming temperature is within the above range, the heat sealability is good.

[0087] As the ethylene-based ionomer, for example, Chemipearl S100, S111, S120, S650, S200, S300, S420, and S500 manufactured by Mitsui Chemicals can be used.

[0088] <Formation of heat seal layer> The heat seal layer can be formed, for example, by printing the heat seal agent on the paper substrate surface opposite to the surface protective layer, and then drying and removing the volatile components. As the printing method, gravure printing and flexographic printing are suitable. For example, in gravure printing, the agent is diluted with a diluting solvent to an appropriate viscosity and concentration as necessary, and is supplied to each printing unit alone or in a mixture, and then applied, and the coating is fixed by drying in an oven to obtain a heat seal layer. The resin content of the heat seal layer is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, based on 100% by mass of the heat seal layer. When it is in the above range, the heat sealability is good. The thickness of the heat seal layer is preferably 0.1 to 10 μm, more preferably 2 to 7 μm.

[0089] [Paper base layer] The paper substrate layer is not particularly limited, and known ones can be used, for example, nonwoven fabric, medium-quality paper, wood-free paper, newsprint, Yupo paper, various coated papers, lining paper, impregnated paper, cardboard, art paper, cast paper, one-sided glossy kraft paper, bleached kraft paper, unbleached kraft paper, coated board, ivory paper, card paper, cup base paper, cast paper, light-shielding paper, and surface-treated paper substrates thereof can be mentioned. In addition, the paper substrate can also be a deposition paper substrate in which an inorganic compound such as silica, alumina, or aluminum is deposited on the paper substrate, and an anchor layer may be used to uniformly form the deposition layer on the paper substrate, and the deposition layer may further be coated with polyvinyl alcohol or the like. Furthermore, a paper substrate in which a heat-sealable resin such as polyethylene is formed on the deposition layer may be used. In addition, various melamine papers in which the paper substrate is impregnated with melamine resin can be used. Among the above, one-sided glossy kraft paper, bleached kraft paper, unbleached kraft paper, and non-coated paper without a coating layer such as a deposition layer are preferable. The paper base material has an average basis weight of 50 to 300 g / m 2 It is preferable that the thickness is 60 to 150 g / m 2 More preferably, the thickness is 60 to 120 g / m 2 It is more preferable that:

[0090] [Barrier layer] The packaging material of the present invention has a barrier layer. The barrier layer improves the water vapor barrier property after folding and also improves the gloss value. In particular, when the barrier layer is in contact with a paper substrate, the barrier layer fills the gaps in the paper substrate, thereby reducing the light transmittance of the entire packaging material and tending to improve the gloss value. In addition, when the barrier layer is located between the paper substrate and the printing layer, or between the paper substrate and the surface protective layer, the barrier layer improves the smoothness of the printing layer and / or the surface protective layer, tending to improve the gloss value. The barrier layer is preferably located between the paper substrate and the heat seal layer, and an inorganic compound layer can be formed on the paper substrate by known methods such as coating and drying a barrier coating agent described below, vacuum deposition, sputtering, etc. Alternatively, an aluminum layer can be formed as a barrier layer by laminating an aluminum foil on the paper substrate by dry lamination or extrusion lamination. The thickness of the barrier layer is preferably 0.01 to 45 μm, more preferably 0.1 to 25 μm, even more preferably 1 to 20 μm, and particularly preferably 5 to 15 μm.

[0091] The barrier layer preferably contains at least one selected from the group consisting of polyvinyl alcohol-based resins, styrene-based resins (C), acrylic-based resins (D'), aluminum, and inorganic oxides, more preferably contains at least one selected from the group consisting of polyvinyl alcohol-based resins, styrene-based resins (C), and acrylic-based resins (D'), and more preferably contains a polyvinyl alcohol-based resin. From the viewpoint of water vapor barrier properties, the barrier layer preferably further contains an inorganic layered filler and / or a hydrocarbon wax.

[0092] <Polyvinyl alcohol resin> The polyvinyl alcohol-based resin may be any resin having structural units derived from vinyl alcohol, and it is also preferable that the polyvinyl alcohol-based resin further contains structural units derived from ethylene. Examples of polyvinyl alcohol resins include polyvinyl alcohol resins and ethylene-vinyl alcohol copolymer resins, with polyvinyl alcohol resins and / or ethylene-vinyl alcohol copolymer resins being preferred, and ethylene-vinyl alcohol copolymer resins being more preferred.

[0093] The content of ethylene-derived structural units in the ethylene-vinyl alcohol copolymer resin is preferably 1 to 40 mol%, more preferably 3 to 20 mol%, and even more preferably 5 to 15 mol%. When the content of ethylene-derived structural units is within the above range, the water vapor barrier property after bending is good. The degree of polymerization of the polyvinyl alcohol resin is preferably 100 to 3,000, and more preferably 500 to 2,400. When within the above range, the water vapor barrier property after bending is good.

[0094] The polyvinyl alcohol resin may have a modified functional group, and examples of the functional group include, but are not limited to, a carbonyl group, a silicon group, etc. Also, the polyvinyl alcohol resin may be crosslinked with a crosslinking agent, and examples of the crosslinking agent include known crosslinking agents such as an isocyanate crosslinking agent, an epoxy crosslinking agent, a melamine crosslinking agent, an oxazoline crosslinking agent, and a silane coupling crosslinking agent, and the oxazoline crosslinking agent and the silane coupling crosslinking agent are preferred.

[0095] The degree of saponification of the polyvinyl alcohol resin is represented by the following formula (1), and is preferably 80 mol% or more, more preferably 90 mol%, and more preferably 95 mol%. When it is in the above range, the water vapor barrier property after bending is good. (Formula 1) Saponification degree: (number of hydroxyl groups) / {(number of hydroxyl groups)+(number of acetate groups)}×100 [mol %]

[0096] As the polyvinyl alcohol-based resin, Kuraray Poval R series (manufactured by Kuraray Co., Ltd., polyvinyl alcohol resin), Kuraray Eval L104B, F104B (manufactured by Kuraray Co., Ltd., ethylene-vinyl alcohol copolymer resin), etc. can be used.

[0097] <Styrene-based resin (C) (excluding acrylic resin (D'))> The styrene resin (C) used in the present invention can be one synthesized by a known method using a known styrene monomer, and among them, a styrene block copolymer is preferable. However, acrylic resin (D') is excluded. The copolymer generally has a polystyrene block and a rubber intermediate block, and the polystyrene part forms a physical crosslink (domain) and becomes a crosslinking point, and the intermediate rubber block gives the product rubber elasticity. The intermediate soft segment includes polybutadiene (B), isobutylene (IB), polyisoprene (I) and polyolefin elastomer (ethylene propylene, EP), etc., and is divided into linear type and radial type depending on the arrangement with the hard segment polystyrene (S). Among the above-mentioned preferred styrene-based resins (C), the present invention may more specifically include at least one selected from the group consisting of styrene-isobutylene-styrene block copolymers (SIBS), styrene-isoprene-styrene block copolymers (SIS), styrene-ethylene-propylene-styrene block copolymers (SEPS), styrene-butylene-styrene block copolymers (SBS), styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-butadiene-isoprene-styrene block copolymers (SBIS), styrene-ethylene-ethylene-isoprene-styrene block copolymers (SEEPS), and styrene-butadiene block copolymers (SB), as well as their acid-modified, acid anhydride-modified, and amine-modified forms. However, the present invention is not limited to these resins, but it is preferable that the styrene-based resin (C) is compatible with the hydrocarbon wax in the ink when the ink is made by adding a solvent described later.Among these, at least one selected from the group consisting of styrene-isobutylene-styrene block copolymer (SIBS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-ethylene-butylene-styrene block copolymer (SEBS), and styrene-ethylene-ethylene-isoprene-styrene block copolymer (SEEPS), as well as acid-, acid anhydride-, and amine-modified versions thereof, is preferred, and at least one selected from the group consisting of styrene-isobutylene-styrene block copolymer (SIBS), and styrene-ethylene-butylene-styrene block copolymer (SEBS), as well as acid-, acid anhydride-, and amine-modified versions thereof is more preferred.

[0098] The weight average molecular weight of the styrene resin (C) is preferably 10,000 to 200,000, more preferably 30,000 to 170,000, and even more preferably 60,000 to 130,000. When it is within the above range, the water vapor barrier property after bending is improved. The styrene content of the styrene resin (C) is preferably 5 to 65 mass%, more preferably 15 to 50 mass%, and even more preferably 25 to 35 mass% in 100 mass% of the styrene resin (C). When it is within the above range, the water vapor barrier property after bending is improved. The content of the acid modified product, acid anhydride modified product, and amine modified product of the styrene resin (C) is preferably 0.01 to 10 mass%, more preferably 0.1 to 5 mass%, and even more preferably 0.5 to 3 mass% in 100 mass% of the styrene resin (C). When it is within the above range, the water vapor barrier property after bending is improved.

[0099] Examples of commercially available styrene-based resins (C) include FG1901, FG1924, G1650, D1117, G1643, FG1924, and MD1648 manufactured by Kraton Corporation; AR-GB-40, AR-1040, AR-NF0-80B, AR-815, and AR-8050NC manufactured by Aron Chemical Industries, Ltd.; SEPTON1020, SEPTON2002, SEPTON2063, and SEPTON HG-252 manufactured by Kuraray Co., Ltd.; Asaprene T-411, Tuftech H1401, Tuftech H1517, and Tuftech MP10 manufactured by Asahi Kasei Corporation; JSRSIS5002 and JSRSIS5506 manufactured by JSR Corporation; and SIBSTAR072T, SIBSTAR073T, and SIBSTAR102T manufactured by Kaneka Corporation.

[0100] <Acrylic resin (D')> The acrylic resin (D') has an acrylic monomer constituent unit. It is also preferable that the acrylic resin is obtained by copolymerizing a styrene-based monomer, a maleic acid-based monomer, or the like. The acrylic resin preferably has a carboxyl group and is made water-soluble in the presence of an emulsifier and / or a basic compound. The acrylic resin (D') may be the same as the acrylic resin (D).

[0101] As the acrylic monomer, any acrylic monomer can be used, and among them, preferred examples include alkyl esters of (meth)acrylic acid, alkyl amides of (meth)acrylic acid, hydroxyalkyl esters of (meth)acrylic acid, etc. The alkyl groups constituting the alkyl esters, etc. preferably have 1 to 18 carbon atoms.

[0102] Suitable examples of the styrene-based monomer include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, and the like, and suitable examples of the maleic acid-based monomer include maleic anhydride and maleic acid, which may be in the form of an alkyl ester having 1 to 18 carbon atoms, an alkylamide having 1 to 18 carbon atoms, or a hydroxyalkyl ester having 2 to 4 carbon atoms. Furthermore, the aqueous acrylic resin used in the present invention may further contain, as a reaction component, known monomers other than those mentioned above that are generally used as reaction components for aqueous acrylic resins.

[0103] Using these reaction components, acrylic resins can be produced by known production methods, and can be made aqueous by using known emulsifiers or polymeric protective colloids, or by introducing carboxyl groups into the molecule and neutralizing with a basic compound. Examples of basic compounds include the same ones as those exemplified for polyurethane resins, and among them, amine compounds are preferred, and ammonia is preferred. The acrylic resin is preferably an aqueous emulsion.

[0104] The acid value of the acrylic resin (D') is preferably 10 to 300 mgKOH / g, more preferably 15 to 300 mgKOH / g, and even more preferably 15 to 250 mgKOH / g. This is because the resin has good water solubility and improves the water-resistant friction property by the acid value. The glass transition temperature of the acrylic resin (D') is preferably -20 to 150°C, and even more preferably -10 to 130°C. This is because the water-resistant friction property is improved by the glass transition temperature range. The weight average molecular weight of the acrylic resin (D') is preferably 5,000 to 700,000, more preferably 8,000 to 500,000, and even more preferably 8,000 to 200,000.

[0105] <Hydrocarbon wax> The hydrocarbon wax used in the present invention means an organic substance that is mainly composed of a long-chain alkyl group skeleton, is solid at room temperature, and becomes liquid when heated, and may contain an acid group, an ester group, a hydroxyl group, etc. in the skeleton. By adding such a hydrocarbon wax to the styrene resin (C), it is possible to develop a higher water vapor barrier property after bending than the resin alone. Here, the factor of water vapor barrier property development due to the hydrocarbon wax is presumed as follows. That is, after the barrier coating agent described below is applied to the substrate, it undergoes a heating and drying process to form a water vapor barrier layer, and in the heating and drying process, the hydrocarbon wax contained in the barrier coating agent starts to aggregate and form an aggregate. Furthermore, it is considered that an oriented structure or a crystalline structure derived from the high crystallinity of the hydrocarbon wax is formed on the surface in the process of the aggregation of the hydrocarbon waxes. As a result, a dense wax layer is formed in the water vapor barrier coating layer, especially near the interface and surface, and it is considered that the presence of a hydrophobic and highly crystalline portion that is difficult for water vapor to permeate suppresses the dissolution and diffusion of water vapor, thereby developing excellent water vapor barrier property after bending.

[0106] Specific examples of the hydrocarbon wax include, but are not limited to, one or more selected from the group consisting of natural waxes and synthetic waxes such as paraffin wax, microcrystalline wax, beeswax, montan wax, ozokerite, ceresin, carnauba wax, candelilla wax, beeswax, Japan wax, and rice wax. It is preferable that the hydrocarbon wax is uniformly dissolved in the barrier coating agent described below. As commercially available products, natural waxes include paraffin wax and microcrystalline wax manufactured by Nippon Seiro Co., Ltd. and ENEOS Corporation. In addition, synthetic waxes include FT115, FT0165, SX105, and FNP0090 manufactured by Nippon Seiro Co., Ltd., CERAMER polymer, POLYWAX polyethylene, UNICID carboxylic acid, UNILIN alcohol, UNITHOX ethoxylate, PETROLITE copolymer, and VYBAR polymer manufactured by Mitsubishi Chemical Corporation, and SANWAX series and VISCOL series manufactured by Sanyo Chemical Co., Ltd. Furthermore, the hydrocarbon wax of the present invention also includes oxidized waxes produced by subjecting these raw materials to chemical reactions such as oxidation, saponification, esterification, maleinization, and acid anhydride conversion, blended waxes in which these waxes are blended with resins, etc., and emulsion waxes in which these waxes are dispersed in water.

[0107] In order for the hydrocarbon wax to exhibit good water vapor barrier properties after bending, the melting point of the hydrocarbon wax is preferably 30°C or more and 110°C or less, and more preferably 40°C or more and 90°C or less. In addition, it is preferable that 80% or more of the hydrocarbon wax has a straight chain structure without branches, and more preferably 0% or more has a straight chain structure without branches. When it is in the above range, the crystallinity of the hydrocarbon wax is improved, so that the water vapor barrier properties after bending are good. In addition, as a hydrocarbon material that is solid at room temperature and has a melting point of 30°C to 110°C and shows similar properties, wax-like olefins having double bonds in the molecule are also included in the hydrocarbon wax, and mixtures of these can be exemplified. Among the above-mentioned hydrocarbon waxes, paraffin wax and microcrystalline wax are preferred, and paraffin wax is most preferred. These waxes have excellent crystallinity, and therefore can particularly promote the formation of a wax aggregate structure in the water vapor barrier composition of the present invention, making it possible to improve the water vapor barrier properties after bending.

[0108] The hydrocarbon wax is preferably 5 to 50% by mass, and more preferably 10 to 50% by mass, when the total solid content of the water vapor barrier layer is taken as 100% by mass. By being in this range, it is possible to achieve better water vapor barrier properties after bending.

[0109] <Inorganic oxide> The inorganic oxide used in the present invention is not particularly limited, but alumina, silica, magnesium oxide, zinc oxide, etc. can be used, and among them, alumina and / or silica are preferable. The inorganic oxide may be in the form of particles, or may be in the form of a film formed by a vacuum deposition method or a sputtering method described below. In the case of a particle shape, although there is no particular limit, it is preferable that it is spherical, and the average particle size is preferably 1 to 10 μm, more preferably 1 to 8 μm, and even more preferably 1 to 6 μm.

[0110] <Alumina> As the alumina used in the present invention, the SA30 series and SA40 series manufactured by Nippon Light Metal Co., Ltd. can be used as particulate materials, and the ES series, CS series, and M series manufactured by Shinkosha Co., Ltd. can be used as deposition agents for film shapes. <Silica> As the silica used in the present invention, as a particle-shaped material, the Nipgel series and Nipsil series manufactured by Tosoh Silica Corporation, and the Mizukasil series manufactured by Mizusawa Chemical Industries, Ltd. can be used, and as a deposition agent for a film-shaped material, the silicon dioxide deposition agent manufactured by USTRON Corporation can be used.

[0111] <Inorganic layered filler> The barrier layer preferably contains an inorganic layered filler. The inorganic layered filler here is an inorganic filler that forms a layered structure, and is preferably one that swells and / or cleaves in a solvent, and may be the same as the inorganic oxide described above. It is preferable to combine at least one selected from the group consisting of polyvinyl alcohol resin, styrene resin (C), and acrylic resin (D') with the inorganic layered filler, and the mass ratio of the polyvinyl alcohol resin, styrene resin (C), and acrylic resin (D') to the inorganic layered filler is preferably 9:1 to 4:6, more preferably 8:2 to 5:5, and even more preferably 8:2 to 6:4. When the mass ratio is within the above range, the water vapor barrier property after bending is good.

[0112] The average particle size of the inorganic layered filler measured by a laser light scattering method is preferably 0.1 to 30 μm, more preferably 0.5 to 15 μm, further preferably 1 to 10 μm, and particularly preferably 1.5 to 5 μm. In the present invention, the average particle size was measured using MT3300EX II manufactured by Microtrac MRB.

[0113] The aspect ratio of the inorganic layered filler is preferably 10 to 2000, more preferably 50 to 1000, and further preferably 200 to 700. The aspect ratio refers to a value measured with a scanning electron microscope (SEM), and in the present invention, the measurement was performed using a JEOL JSM-7800F.

[0114] The specific surface area of ​​the inorganic layered filler is 0.5 to 250 m 2 / g, and 1 to 100m 2 / g is more preferable, and 3 to 50m 2 More preferably, the range is 5 to 30 m / g. 2 The specific surface area is a value calculated from the amount of nitrogen gas adsorbed by the BET method, and in the present invention, it was measured using a TriStar2 manufactured by Shimadzu Corporation.

[0115] Preferred examples of the inorganic layered filler include montmorillonite, beidellite, saponite, hectorite, sauconite, vermiculite, mica, paragonite, lepidolite, margarite, clintonite, anandite, chlorite, donbassite, sudoite, cookeite, clinochlore, chamosite, nimite, tetrasilylic mica, talc, pyrophyllite, nacrite, kaolinite, halloysite, chrysotile, sodium teniolite, xanthophyllite, antigorite, dickite, hydrotalcite, etc., and one or more selected from the group consisting of kaolin, montmorillonite, and mica are preferred, and montmorillonite is more preferred. Montmorillonite has high water absorption and high viscosity after swelling due to its layered structure, so that resin easily penetrates between the layers of the layered filler, contributing to improving the water vapor barrier property of the packaging material after folding.

[0116] These inorganic layered fillers may be naturally occurring or artificially synthesized or modified, or may be treated with an organic substance such as an onium salt.

[0117] The content of the inorganic layered filler is preferably from 1 to 40 mass %, more preferably from 10 to 35 mass %, and further preferably from 20 to 30 mass %, relative to 100 mass % of the barrier layer.

[0118] <Montmorillonite> The above montmorillonite is represented by the following formula 2. Bentonite, which contains montmorillonite as a main component and further contains minerals such as quartz and feldspar, can also be preferably used. (Formula 2) M a Si4(Al 2-a Mg a )O 10 (OH)2 nH2O (In formula 2, M represents a sodium cation, and a is 0.25 to 0.60. The number of water molecules bonded to the ion-exchangeable cations between layers can vary depending on the cation species, humidity, and other conditions, and is therefore represented by nH2O in the formula.)

[0119] Montmorillonite also includes isomorphous ion-substituted products of magnesian montmorillonite, iron montmorillonite, and iron magnesian montmorillonite, which are represented by the following formulas (3) to (5), and these may also be used. (Formula 3) M a Si4(Al 1.67-a Mg 0.5+a )O 10 (OH)2 nH2O (Formula 4) M a Si4(Fe 2-a3 +Mg a )O 10 (OH)2 nH2O (Formula 5) M a Si4(Fe 1.67-a3 +Mg 0.5+a )O 10 (OH)2 nH2O (In formulas 3 to 5, M represents a sodium cation, and a is 0.25 to 0.60.)

[0120] Montmorillonite usually has cations between its layers, but the content varies depending on the place of origin. Examples of the ions include inorganic cations such as sodium ions, calcium ions, magnesium ions, and potassium ions, and organic cations such as quaternary ammonium ions. From the viewpoint of affinity with water, inorganic cations are preferred, and sodium ions and / or calcium ions are more preferred. It is also preferred to use montmorillonite that has been purified by water treatment.

[0121] The average particle size of the montmorillonite is preferably from 0.1 to 10 μm, more preferably from 1 to 5 μm, and even more preferably from 1.5 to 3 μm. The particle aspect ratio of the montmorillonite is preferably 10-2,000, more preferably 100-1,000, and further preferably 300-700. The specific surface area of ​​montmorillonite is 1 to 250 m 2 / g, and 1 to 100m 2 / g is more preferable, and 3 to 50m 2 More preferably, the range is 5 to 30 m / g. 2 It is particularly preferred that the molecular weight is 1 / g.

[0122] The average thickness of the montmorillonite particles is preferably from 0.05 to 30 nm, more preferably from 0.1 to 10 nm, and even more preferably from 0.5 to 3 nm. The average major axis of the montmorillonite particles is preferably from 0.01 to 5 μm, more preferably from 0.05 to 3 μm, and even more preferably from 0.1 to 1 μm. Here, the average thickness and the average major axis of the particles refer to values ​​measured with an atomic force microscope (AFM), and in the present invention, the measurements were performed using an AFM100Plus manufactured by Hitachi High-Technologies Corporation.

[0123] As the montmorillonite, commercially available products such as Kunipia-F and Kunipia-G (manufactured by Kunimine Kogyo Co., Ltd.) can be used.

[0124] <Kaolin> Kaolin is mainly composed of kaolinite (Al2O3·2SiO2·H2O) or halloysite (Al2O3·2SiO2·2H2O), and may be natural or synthetic. Depending on the manufacturing method, there are dry kaolin, wet kaolin, calcined kaolin, etc., but it is not limited to any of them.

[0125] From the viewpoint of water vapor barrier properties after folding, the average particle size of kaolin is preferably from 0.1 to 30 μm, more preferably from 0.2 to 20 μm, and even more preferably from 0.3 to 10 μm. The aspect ratio of kaolin is preferably 10-1,000, more preferably 30-500, and further preferably 50-200. The specific surface area of ​​kaolin is 1 to 250 m 2 / g, and 1 to 100m 2 / g is more preferable, and 3 to 50m 2 More preferably, the range is 5 to 30 m / g. 2 It is particularly preferred that the molecular weight is / g.

[0126] As the kaolin, commercially available products such as Varisurf HX (manufactured by Imerys), NN kaolin clay, and ST kaolin clay (manufactured by Takehara Chemical Industry Co., Ltd.) can be used.

[0127] <Mica> Both natural and synthetic mica can be used. Natural mica is a scaly base material made by crushing mica ore, and the particle size and aspect ratio can be controlled by mechanical crushing, sintering, etc. Synthetic mica includes those synthesized by heating industrial raw materials such as SiO2, MgO, Al2O3, K2SiF6, Na2SiF6, melting them at a high temperature of about 1500°C, and then cooling and crystallizing them. Compared to natural mica, it has fewer impurities and is more uniform in size and thickness. Specifically, fluorphlogopite (KMg3AlSi3O10F2), potassium tetrasilicic mica (KMg 25 AlSi4O10F2), sodium tetrasilicic mica (NaMg25 AlSiO 10 F2), Na taeniolite (NaMg2LiSi4O10F2), LiNa taeniolite (LiMg2LiSi4O 10 F2) are known. From the viewpoint of dispersibility, synthetic mica that is easy to cleave by intercalation is preferable.

[0128] From the viewpoint of water vapor barrier properties after folding, the average particle size of the mica is preferably 30 μm or less, more preferably 1 to 25 μm, and even more preferably 5 to 15 μm. The aspect ratio of the mica is preferably 30-200, more preferably 70-170, and further preferably 100-150. The specific surface area of ​​mica is 1 to 250 m 2 / g, and 1 to 100m 2 / g is more preferable, and 3 to 50m 2 More preferably, the range is 5 to 30 m / g. 2 It is particularly preferred that the molecular weight is / g.

[0129] As the mica, commercially available products such as Mica Powder TM series, Mica Powder NCF series (manufactured by Yamaguchi Mica Co., Ltd.), L60M, L100M (manufactured by Seishin Enterprise Co., Ltd.) and the like can be used.

[0130] <Additives that can be included in the barrier layer> The barrier layer may contain known additives such as an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity adjuster, a colorant, etc., within the scope of not impairing the effects of the present invention.

[0131] <Coating method of barrier coat layer by coating and drying> The barrier coat layer can be formed by a coating method involving coating and drying, for example, by printing a barrier coating agent on the surface of a paper substrate, and then drying to remove the volatile components. As a printing method, gravure printing and flexographic printing are suitable. For example, in gravure printing, the agent is diluted with a diluting solvent to an appropriate viscosity and concentration as necessary, and is supplied to each printing unit alone or in a mixture, and then applied, and the coating is fixed by drying in an oven to obtain a barrier layer.

[0132] <Vacuum deposition method> The vacuum deposition method is a method of depositing a metal such as aluminum by high-frequency induction heating, direct current heating, or electron beam heating at 1200 to 1500°C for 10 -1 ~10 -2 This method involves vapor deposition under conditions of about Pa. Before vacuum deposition, the object to be deposited can be subjected to a treatment for improving adhesion, such as a corona discharge treatment, on the surface. From the viewpoints of water vapor barrier properties after folding, light blocking properties, and economic efficiency, the thickness of the metal film formed by vacuum deposition is preferably 10 to 300 nm.

[0133] <Sputtering method> The sputtering method is 10 -1 ~10 -2 The bonding is carried out by introducing an inert gas such as Ar and applying a voltage under conditions of about Pa. The thickness of the metal film formed is preferably 10 to 300 nm from the viewpoints of water vapor barrier properties after bending, light blocking properties, and economic efficiency.

[0134] [Adhesive layer] The packaging material of the present invention preferably has an adhesive layer. The adhesive layer can be formed by applying the following adhesive. As the adhesive, a two-liquid reactive adhesive, an acrylic adhesive, an anchor coating agent, a meltable polyolefin resin, etc. are preferably used, but are not limited to these. Among them, it is preferable to form the adhesive layer by a dry lamination method using a two-liquid reactive adhesive, or an extrusion lamination method using an anchor coating agent and a meltable polyolefin resin.

[0135] <Dry lamination method> The dry lamination method is a method of applying a two-liquid reactive adhesive consisting of polyol and polyisocyanate, which is diluted with an organic solvent to an appropriate viscosity, applied to the printed surface of the obtained printed matter, dried, and laminated by pressing with a sealant. Examples of such adhesives include TM-250HV / CAT-RT86L-60, TM-550 / CAT-RT37, and TM-314 / CAT-14B manufactured by Toyo-Morton Co., Ltd.

[0136] <Extrusion lamination method> The extrusion lamination method is a method in which meltable polyolefin resin is extruded into a film form from a slit-shaped device called a T-die, laminated on a substrate, and then bonded to another substrate. In the case of printed matter, an anchor coating agent is often applied to the printed layer before extrusion lamination. Meltable polyolefin resin can also be extruded onto the printed surface of a printed matter and a sealant can be bonded at the same time. As anchor coating agents, imine-based, butadiene-based, and isocyanate-based anchor coating agents can be used. Specific examples include EL-420 (imine-based), EL-452 (butadiene-based), EL-530A / B (isocyanate-based), and EL-540 / CAT-RT32 (isocyanate-based) manufactured by Toyo-Morton Co., Ltd. Meltable polyolefin resins include low-density polyethylene, polypropylene, and ethylene-vinyl acetate copolymers. Specific examples include Novatec LD LC600A (low-density polyethylene) manufactured by Japan Polyethylene Co., Ltd.

[0137] [Anchor coat layer] The packaging material of the present invention preferably has an anchor coat layer. When the packaging material has an anchor coat layer, the anchor coat layer is preferably located between the paper base layer and the heat seal layer, and can be formed by a known method such as gravure printing or flexographic printing.

[0138] The anchor coat layer preferably contains an acrylic resin, and the acrylic resin is preferably an acrylic resin emulsion, and more preferably a styrene-acrylic resin emulsion.

[0139] <Formation of anchor coat layer> The anchor coat layer can be formed, for example, by printing the substrate with an anchor coat agent and then removing the volatile components. The printing method includes a flexographic printing method, in which, for example, the anchor coat agent is diluted with a diluting solvent to a viscosity and concentration suitable for flexographic printing, and is supplied to each printing unit alone or in a mixture and applied. The coating is then fixed by drying in an oven or the like to obtain an anchor coat layer.

[0140] <Preferable form for achieving gloss value of surface protective layer> As a preferred embodiment for achieving the gloss value of the surface protective layer, the thickness of the surface protective layer is preferably 0.3 to 10 μm, the solid content of the styrene-acrylic copolymer resin (A) is preferably 50 mass% or more of the total mass of the solid contents of the surface protective layer, the styrene-acrylic copolymer resin (A) preferably has an acid group, in which case the acid value is preferably 20 to 200 mgKOH / g, and the content ratio of the styrene monomer-derived structure in 100 mass% of the surface protective layer is preferably 5 mass% or more. In addition, the film thickness of the printed layer is preferably 0.5 to 5 μm, the total solid content of the styrene-acrylic copolymer resin (B) and the styrene-maleic acid copolymer resin is preferably 50 mass% or more of the total solid mass of the resin contained in the printed layer, and the content ratio of styrene monomer-derived structures in 100 mass% of the printed layer is preferably 5 mass% or more. Furthermore, the basis weight of the paper base material is 50 to 300 g / m 2 It is preferable that: In addition, the barrier layer is preferably in contact with the paper substrate, the thickness of the barrier layer is preferably 0.01 to 45 μm, and the barrier layer preferably contains at least one selected from the group consisting of polyvinyl alcohol resins, styrene resins (C), acrylic resins (D'), aluminum, and inorganic oxides. The gloss value tends to improve by increasing the film thickness of each layer, the content ratio of the styrene monomer-derived structure in each layer, and the basis weight of the paper base material within their respective preferred ranges. In addition, it is more preferable that the barrier layer contains at least one selected from the group consisting of polyvinyl alcohol resins, styrene resins (C), and acrylic resins (D'). When these resins are contained, the voids in the paper fibers are easily filled, so the gloss value tends to improve. Furthermore, the higher the basis weight of the paper base material, the fewer the voids in the paper fibers, and the more the smoothness of the printing layer and the surface protection layer is improved, so the gloss value also tends to improve. By adjusting the combination of conditions that are effective for the gloss value described above and by adjusting each condition, the target gloss value can be achieved.

[0141] <Manufacturing method of packaging materials> The present invention relates to a method for producing a packaging material having a heat seal layer, a paper base material, a printing layer, and a surface protective layer in this order, the method including the steps of printing a printing ink on one side of the paper base material to form a printing layer, printing an overcoat agent containing a styrene-acrylic copolymer resin (A) on the printing layer to form a surface protective layer, and applying a heat seal agent to the other side of the paper base material to form a heat seal layer. The order of the steps does not matter, but it is preferable to form the printing layer, the surface protective layer, and the heat seal layer in this order.

[0142] The manufacturing method of the packaging material will be described by taking a configuration of a heat seal layer / barrier layer / adhesive resin layer / paper base material layer / printing layer / surface protection layer as an example. However, the configuration of the packaging material in the present invention is not limited to the above.

[0143] First, the paper base material (unbleached kraft paper: kraft paper made from unbleached kraft pulp (Nippon Paper Industries, unbleached kraft K, basis weight 70 g / m 2 ) and apply dry lamination adhesive TM-250HV / CAT-RT86L-60 at a rate of 4g / m 2 Then, aluminum foil is laminated to form a barrier layer. A heat seal agent containing an ethylene-vinyl acetate copolymer resin and / or an acrylic resin is applied onto the barrier layer to form a heat seal layer. Thereafter, a printing ink is printed on the side of the paper substrate that does not have the barrier layer to form a printed layer, and an overcoat agent is printed to form a surface protective layer, thereby producing a packaging material having a configuration of heat seal layer / barrier layer / adhesive resin layer / paper substrate layer / printed layer / surface protective layer.

[0144] [Packaging bag] The packaging material in the present invention is cut to a predetermined size, and the edges are heat-sealed in a state where the heat-sealable layers are joined together to form a packaging bag. The heat-sealing temperature is preferably 50 to 250°C, and more preferably 80 to 180°C. The heat-sealing pressure is 1 to 5 kg / cm. 2 The conditions are as follows. One sheet of packaging material may be folded and the edges may be heat sealed, or two or more sheets of packaging material may be heat sealed. Also, the packaging bag may be one in which all openings are heat sealed after the contents are packed. This packaging bag can be widely used as a packaging bag for food, medicine, etc.

[0145] <Acid value> The acid value is the number of milligrams of potassium hydroxide required to neutralize the free fatty acids, resin acids, etc. contained in 1 g of a sample, and was measured by the method described in JIS K 0070. EXAMPLES

[0146] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted. In addition, "NV." represents the mass % of non-volatile content.

[0147] <Preparation Example 1> (Preparation of urethane resin solution PU1) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 227.0 parts of polyester polyol, which is a condensate of adipic acid and 3-methyl-1,5-pentanediol, 9.6 parts of PEG (polyethylene glycol with a number average molecular weight of 2000), 30.1 parts of 2,2-dimethylolpropanoic acid (DMPA), and 250 parts of methyl ethyl ketone (MEK) were mixed and stirred while dropping 90.6 parts of isophorone diisocyanate (IPDI) over 1 hour, and reacted at 80 ° C for 4 hours to obtain a terminal isocyanate prepolymer, and a terminal isocyanate prepolymer solution was obtained. A mixture of 2.7 parts of 2-aminoethylethanolamine (AEA) and 150 parts of isopropanol (IPA) was gradually added to the obtained terminal isocyanate prepolymer solution at room temperature, and reacted at 40 ° C for 2 hours to obtain a solvent-based polyurethane resin solution. Next, 38.1 parts of 10% ammonia water and 801.4 parts of ion-exchanged water were gradually added to the solvent-based polyurethane resin solution to neutralize and make it water-soluble, and then 0.5 parts of an antifoaming agent was added and the MEK and IPA were distilled off under reduced pressure. Water was then added to adjust the solids content, yielding a urethane resin solution PU1 with a solids content of 28% and a weight average molecular weight of 38,000.

[0148] <Production Example 1> (Production of printing ink K1) A mixture of 25.9 parts of water, 18 parts of Pigment Black 7, 5 parts of urea, and 15 parts of styrene-acrylic copolymer resin (A) solution SAC1 (acid value: 213 mg KOH / g, weight average molecular weight: 8000, glass transition temperature: 73°C, solid content: 28%, content of styrene monomer derived structure: 30 mass%) was kneaded and dispersed using a bead mill, and then 32.7 parts of styrene-acrylic copolymer resin (A) emulsion SAC2 (hydroxyl value: 36 mg KOH / g, glass transition temperature: 14°C, solid content: 40%, content of styrene monomer derived structure: 32 mass%) and 3 parts of polyethylene wax were added and mixed by stirring to obtain printing ink K1.

[0149] <Production Examples 2 to 9, Comparative Production Examples 10 and 11> (Production of Printing Inks K2 to K11) Printing inks K2 to K11 were obtained in the same manner as in Production Example 1, except that the raw materials and blending ratios shown in Table 1-1 were used. The properties of the raw materials used are as follows. Styrene-maleic acid copolymer resin solution SMA1 (acid value: 140 mg KOH / g, glass transition temperature: 83°C, solid content: 28%, content of styrene monomer-derived structure: 25% by mass) Acrylic resin AC1 (AW-36H, manufactured by Seiko PMC Co., Ltd., acid value: 62 mg KOH / g, glass transition temperature: 53°C, solid content: 28%) Urethane resin emulsion PU2 (WBR016U, manufactured by Taisei Fine Chemical Co., Ltd., acid value: 7 mg KOH / g, solid content: 40%) Acrylic resin emulsion AC2 (acid value: 215 mg KOH / g, weight average molecular weight: 8500, glass transition temperature: 85°C, solid content: 40%)

[0150] <Production Example 10> (Production of Overcoat Agent V1) 4.3 parts of water, 87.6 parts of styrene-acrylic copolymer resin (A) emulsion SAC3 (acid value 100 mg KOH / g, glass transition temperature: 16°C, solids content 40%, content of styrene monomer derived structure 31% by mass), and 8.1 parts of polyethylene wax were added and mixed by stirring to obtain overcoat agent V1.

[0151] <Production Examples 11 to 13, Comparative Production Examples 3 and 4> (Production of Overcoat Agents V2 to V6) Overcoat agents V2 to V6 were obtained in the same manner as in Production Example, except that the raw materials and compounding ratios shown in Table 1-2 were used. The properties of the raw materials used are as follows. Styrene-acrylic resin emulsion SAC4 (acid value: 40 mg KOH / g, glass transition temperature: 49°C, solid content: 40%, content of styrene monomer-derived structure: 30% by mass) Styrene-acrylic resin emulsion SAC5 (glass transition temperature: 22°C, solid content: 40%, content of styrene monomer-derived structure: 33% by mass)

[0152] [Table 1-1]

[0153] [Table 1-2]

[0154] (Anchor Coat Agent ACC1) ACC1: Anchor coating agent containing styrene acrylic resin emulsion (acid value 100 mg KOH / g, glass transition temperature 30°C, solid content 50% by mass)

[0155] (Heat sealant H1~H5) H1: Heat sealant containing ethylene vinyl acetate copolymer resin (Japan Coating Resins, Aquatex MC3800, minimum film-forming temperature: 100°C, solid content 50% by mass) H2: A heat sealant containing acrylic resin (acid value 100 mgKOH / g, glass transition temperature 20°C, solid content 48% by mass) H3: Heat sealant containing ethylene acrylic copolymer resin (Japan Coating Resins, Aquatex AC3100, minimum film-forming temperature: 100°C, solid content 44.5% by mass) H4: Heat sealant containing ethylene ionomer (Mitsui Chemicals, Chemipearl S100, minimum film-forming temperature: 65°C, solid content 27% by mass) H5: Heat sealant containing urethane resin (solid content 30%, hydroxyl value 3.8 mgKOH / g, amine value 8.5 mgKOH / g, weight average molecular weight 48,000)

[0156] (Manufacturing of barrier coating agents) <Production Example 14> (Production of Barrier Coating Agent X1) 6 parts of polyvinyl alcohol resin PVA1 (manufactured by Kuraray, Exeval AQ-4104, ethylene vinyl alcohol resin, ethylene content: 6 mol%, solid content: 100%) and 92 parts of mixed solvent (water / IPA=8 / 2) were heated with stirring, and the heating and stirring were continued at 95°C for 1 hour, after which the heating was stopped and the stirring was continued until the temperature returned to normal, to obtain an aqueous solution of polyvinyl alcohol resin PVA1. Montmorillonite (swelling, average particle size: 2 μm, aspect ratio: 500, specific surface area: 13.1 m) was added to the aqueous solution of polyvinyl alcohol resin PVA1. 2 / g, particle thickness: 1 nm, average major axis: 500 nm, solid content 100%) were added and mixed and stirred to obtain barrier coating agent X1 (solid content 8%).

[0157] <Production Example 15> (Production of Barrier Coating Agent X2) A styrene-based block copolymer (Kaneka Corporation, product name: SIBSTAR 062T (styrene-isobutylene-styrene block copolymer) 20 parts, a hydrocarbon-based wax WAX (F-1) 10 parts, and a solvent MCH (methylcyclohexane) (δd: 16.0, δp: 0) 68 parts were heated with stirring and continued to be heated and stirred at 80°C for 1 hour, after which the heating was stopped and stirring was continued until the temperature returned to room temperature, to obtain a styrene-based block copolymer solution. To the styrene-based block copolymer solution, 2 parts of amorphous silica (Mizukasil P707, manufactured by Mizusawa Industrial Chemicals) were added and mixed and stirred to obtain a barrier coating agent X2 (solid content 32%).

[0158] <Production Example 16> (Production of Barrier Coating Agent X3) 75 parts of acrylic resin (BASF Ltd., product name: Joncryl HPB1634, modified styrene acrylic emulsion, solid content: 40%) and 25 parts of paraffin wax (BYK Ltd., product name: AQUACER497) were added and mixed with stirring to obtain a barrier coating agent X3 (solid content 55%).

[0159] <Production Example 17> (Production of Barrier Coating Agent X4) 100 parts and 75 parts of urethane resin PU1 and 25 parts of paraffin wax (BYK product name: AQUACER497) were mixed and stirred to obtain a barrier coating agent X4 (solid content 55%).

[0160] Example 1 (Production of Laminate P1) Next, unbleached kraft paper: kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., unbleached kraft K, basis weight 100 g / m 2 ) was printed with printing ink K1 at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried for 10 seconds with a 1200 W dryer to form a printed layer (thickness 2 μm). Overcoat agent V1 was printed on the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried at 25° C. for 12 hours to obtain an intermediate laminate p1 having a paper substrate / printed layer / surface protective layer configuration. Aluminum foil (thickness 6 μm) was bonded to the side of the substrate opposite the printed layer in the intermediate laminate p1 by extrusion lamination under the following conditions: adhesive resin: polyethylene (melting point: 120°C), resin temperature: 330°C, coating speed: 80 m / min, coating thickness: 10 μm. Then, heat sealant H1 was printed on the aluminum foil using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm under the following conditions: printing speed: 50 m / min, in-line oven temperature: 70°C, to obtain a packaging material P1 having a configuration of heat seal layer / barrier layer / adhesive resin layer / paper substrate / printed layer / surface protection layer.

[0161] <Examples 2 to 20, Comparative Examples 1 to 7> (Production of packaging materials P2 to 20, P'1 to 7) Packaging materials P2-20 and P'1-7 having the same configuration were prepared in the same manner as the above packaging materials, except that the printing inks and overcoat agents shown in Tables 2-1, 2-2, and 3 were used. The properties of the raw materials used are as follows. Kraft paper (Nippon Paper Industries, double-glazed Kraft K, basis weight 50g / m 2 ) Kraft paper (Nippon Paper Industries, double glazed Kraft K, basis weight 100g / m 2 ) Coated paper (Oji Materia, OK Ball, basis weight 270g / m 2 ) Aluminum-metallized paper (basis weight 100g / m 2 )

[0162] <Example 21> (Production of packaging material P21) Aluminum-deposited paper (basis weight 200 g / m) with an aluminum layer as a barrier layer 2 On the surface opposite to the barrier layer of the paper, a printing ink K1 was printed at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried for 10 seconds with a 1200 W dryer to form a printed layer (thickness 2 μm). On the printed layer, an overcoat agent V1 was printed at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried at 25° C. for 12 hours to obtain an intermediate laminate p21 having a barrier layer / paper substrate / printed layer / surface protective layer configuration. A heat seal agent H1 was printed on the side of the substrate opposite the printing layer in the intermediate laminate p21 using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm at a printing speed of 50 m / min and an in-line oven temperature of 70°C to obtain a packaging material P21 having a configuration of heat seal layer / barrier layer / paper substrate / printed layer / surface protection layer.

[0163] <Example 22> (Production of packaging material P22) 100 parts of barrier coating agent X1 was diluted with a mixed solvent (isopropyl alcohol / water) to a Zahn cup #3 (manufactured by Rigo Co., Ltd.) viscosity of 16 seconds (25° C.). Next, unbleached kraft paper: kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., unbleached kraft K, basis weight 100 g / m 2 ) was printed with printing ink K1 at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried for 10 seconds with a 1200W dryer to form a printed layer (thickness 2 μm). Overcoat agent V1 was printed on the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried at 25° C. for 12 hours to obtain an intermediate laminate p22 having a paper substrate / printed layer / surface protective layer configuration. On the side opposite the printed layer of the substrate in the intermediate laminate p22, the diluted barrier coating agent X1 was printed three times using a gravure printing machine equipped with a gravure plate having a plate depth of 60 μm under conditions of a printing speed of 50 m / min and an in-line oven temperature of 60°C to form a barrier layer (thickness 6 μm), and on top of the barrier layer, a heat seal agent H1 was printed using a gravure printing machine equipped with a gravure plate having a plate depth of 50 μm under conditions of a printing speed of 50 m / min and an in-line oven temperature of 70°C to obtain a packaging material P22 having a configuration of heat seal layer / barrier layer / paper substrate / printed layer / surface protection layer.

[0164] <Examples 23 to 43, Comparative Examples 8 to 16> (Production of packaging materials P23 to 43, P'8 to 16) Packaging materials P23 to 43 and P'8 to 16 having similar configurations were prepared using the same procedures as for preparing the above packaging materials, except that the printing inks, barrier coating agents, and overcoat agents shown in Tables 4-1, 4-2, and 5 were used.

[0165] <Example 44> (Production of packaging material P44) Next, unbleached kraft paper: kraft paper made from unbleached kraft pulp (manufactured by Nippon Paper Industries Co., Ltd., unbleached kraft K, basis weight 100 g / m 2 ) was printed with printing ink K1 at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 250 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried for 10 seconds with a 1200W dryer to form a printed layer (thickness 2 μm). Overcoat agent V1 was printed on the printed layer at a printing speed of 50 m / min using a small flexiproof printer (flexographic printer) equipped with a 200 line / inch anilox roll and a solid plate made of photosensitive resin, and then dried at 25° C. for 12 hours to obtain an intermediate laminate p44 having a paper substrate / printed layer / surface protective layer configuration. In the intermediate laminate p44, a vacuum degree of 8×10 was applied to the opposite side of the printed layer of the substrate. -2 A barrier layer (thickness 6 μm) was formed by vacuum-depositing alumina (purity 99.9% or more) under conditions of Pa and coating thickness of 10 μm, and then heat-sealing agent H1 was printed on the barrier layer using a gravure printing machine equipped with a gravure plate with a plate depth of 50 μm under conditions of a printing speed of 50 m / min and an in-line oven temperature of 70°C, to obtain a packaging material P44 having a configuration of heat-sealing layer / barrier layer / paper base material / printing layer / surface protective layer.

[0166] [Evaluation of packaging materials] Details of the resulting packaging material are given below. The packaging materials P1 to 44 and P'1 to 16 obtained in Examples 1 to 44 and Comparative Examples 1 to 17 were evaluated as described below. The results are shown in Tables 2 to 5. For the Examples and Comparative Examples other than Comparative Examples 4 and 11 which did not have a surface protective layer, the 60 degree gloss value of the surface protective layer was measured by the method described in JIS Z8741:1997.

[0167] <Water friction resistance> The obtained packaging material was cut into a size of 25 mm x 150 mm, and the water friction resistance was evaluated according to the following criteria using a Gakushin-type friction fastness tester manufactured by Tester Sangyo Co., Ltd. Note that A, B, and C are ranges that are acceptable for practical use. Test conditions: Load: 200g, number of reciprocations: 2, paper: 5 drops of water on Kanakin cloth Evaluation Criteria A. The printed layer is not removed and the exposed area of ​​the base paper is less than 1%. B. The paper has a small amount of ink on it. A small amount of the printing layer has been removed, and the exposed area of ​​the base paper is between 1% and 10%. C. The paper has a thin layer of ink on the entire surface. The printed layer has been removed slightly, and the exposed area of ​​the base paper is between 10% and 20%. D. The ink is thickly adhered to the entire surface of the paper. Most of the printing layer has been removed, and the exposed area of ​​the base paper is 20% or more.

[0168] <Heat resistance> The obtained packaging material was cut into a size of 25 mm x 150 mm, and the glossy side of an aluminum foil (thickness: 15 μm) of 25 mm x 150 mm was placed on the surface protective layer, and heat-sealed using the following device and conditions. After peeling off the aluminum foil, the heat resistance was evaluated based on the state of the printed layer according to the following criteria. Note that A, B, and C are ranges that are acceptable for practical use. <Heat sealing conditions> Equipment: Thermal gradient heat sealer [Toyo Seiki Co., Ltd.; TYPE, HG-100], Seal width: 10mm from the bent part, heater temperature: 160℃, Sealing pressure: 2kg / cm 2 , Sealing time: 1sec Evaluation Criteria A. The printed layer is not removed and the exposed area of ​​the base paper is less than 1%. B. The paper has a small amount of ink on it. A small amount of the printing layer has been removed, and the exposed area of ​​the base paper is between 1% and 10%. C. The paper has a thin layer of ink on the entire surface. The printed layer has been removed slightly, and the exposed area of ​​the base paper is between 10% and 20%. D. The ink is thickly adhered to the entire surface of the paper. Most of the printing layer has been removed, and the exposed area of ​​the base paper is 20% or more.

[0169] <Releasability> The obtained packaging material was cut into two pieces of 40 mm square, and the heat seal layer and the surface protection layer of the cut packaging material were overlapped, and the heat seal layer was pressed at a temperature of 40°C and a load of 100 kg / cm using a small heat press machine H30-10D manufactured by AS ONE Corporation. 2 (meaning a significantly excessive load). After leaving it in that state for 12 hours, the two overlapping prints were peeled off, and the peeling state of the print layers was visually observed and evaluated according to the following criteria. AA, A, B, and C are ranges that are acceptable for practical use. Evaluation Criteria AA. The amount of the printed layer transferred to the back side of the unbleached kraft paper is 0% by area, and there is no resistance when peeling off. A. The amount of the printed layer transferred to the back surface of the unbleached kraft paper is greater than 0 area percent and less than 1 area percent. B. The amount of the printed layer transferred to the back surface of the unbleached kraft paper is 1 area % or more and less than 10 area %. C. The amount of the printing layer transferred to the back surface of the unbleached kraft paper is 10% by area or more and less than 20% by area. D. The amount of the printed layer transferred to the back side of the unbleached kraft paper is 20% or more by area.

[0170] <Heat sealability> The obtained packaging material was cut into a size of 15 mm x 100 mm, folded so that the heat-sealed layers overlapped each other, and heat-sealed using the following equipment and conditions. Both unsealed ends were fixed to a small tensile tester to evaluate the heat-seal strength. A, B, and C are ranges that are acceptable for practical use. <Heat sealing conditions> Equipment: Heat seal tester manufactured by Tester Sangyo Co., Ltd., Seal width: from the folded part 10mm, heater temperature: 160℃, sealing pressure: 2kg / cm 2 , Sealing time: 1sec <Heat seal strength measurement conditions> Equipment: Intesco small tensile testing machine (model: IM-20), test piece width: 15 mm, Peeling mode: 90° peeling, tensile speed: 300mm / min Evaluation Criteria A. The heat seal strength is 5.0N or more. B. The heat seal strength is greater than or equal to 3.5N and less than 5.0N. C. The heat seal strength is 1.0N or more and less than 3.5N. D. The heat seal strength is less than 1.0 N.

[0171] <Puncture resistance> The obtained packaging material was cut into 70 mm squares and tested under the following conditions using a method based on JIS1707, and evaluated according to the following criteria, where A, B, and C are ranges that are acceptable for practical use. <Penetration test conditions> Piercing speed: 50mm / min, needle diameter: 1mm, Needle piercing surface: overcoat surface of second laminate Evaluation Criteria A. The puncture strength is 12N or more. B. The puncture strength is greater than or equal to 10N and less than 12N. C. The puncture strength is 5N or more and less than 10N. D. The puncture strength is less than 5N.

[0172] <Water vapor barrier properties after bending> The obtained packaging material was cut into 100 mm squares and folded so that the faces of the base material 2 overlapped, and a load of 1 kg / m2 was applied to the folded portion for 5 seconds. The water vapor barrier properties of the unfolded and unfolded sample were evaluated in accordance with JIS Z0208:1976 (cup method) Method B (temperature 40°C ± 0.5°C, relative humidity 90% ± 2%), with the heat seal layer positioned on the inner side (low humidity side), and the water vapor permeability was measured and evaluated according to the following criteria. Note that A, B, and C are ranges that are acceptable for practical use. A: Water vapor permeability is 50.0g / (m 2 Less than 1 day B: Water vapor permeability is 50.0g / (m 2 ·day) or more, 100.0g / (m 2 Less than 1 day C: Water vapor permeability is 100.0g / (m 2·day) or more, 200.0g / (m 2 Less than 1 day D: Water vapor permeability is 200.0g / (m 2 1 day or more

[0173] [Table 2-1]

[0174] [Table 2-2]

[0175] [Table 3]

[0176] [Table 4-1]

[0177] [Table 4-2]

[0178] [Table 5]

[0179] The present invention provides a packaging material that is excellent in water-friction resistance, heat resistance, releasability, heat sealability and puncture resistance. In particular, Comparative Examples 1 and 8, which did not have a heat seal layer, did not satisfy the heat sealability, Comparative Examples 2 and 9, which contained an acrylic resin in the printing layer, and Comparative Examples 3 and 10, which contained a urethane resin, did not satisfy the standards for releasability and puncture resistance, Comparative Examples 4 and 11, which did not contain a surface protective layer, did not satisfy the water friction resistance, heat resistance, and puncture resistance, Comparative Examples 5 and 12, which contained a polyurethane resin in the surface protective layer, and Comparative Examples 6 and 13, which contained an acrylic resin, did not satisfy the standards for heat resistance, releasability, and puncture resistance, Comparative Examples 7 and 14, which had a gloss value of more than 40, did not satisfy the water friction resistance, and Comparative Example 15, which contained a urethane resin in the barrier layer, and Comparative Example 16, which did not contain a barrier layer, did not satisfy the water vapor barrier property after folding.

Claims

1. A packaging material having a heat seal layer, a barrier layer, a paper base material, a printing layer and a surface protective layer, the surface protective layer comprises a styrene-acrylic copolymer resin (A), the printing layer contains a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin, the barrier layer contains at least one selected from the group consisting of a polyvinyl alcohol-based resin, a styrene-based resin (C), an acrylic-based resin (D'), aluminum, and an inorganic oxide; A packaging material, wherein the surface protective layer has a 60 degree gloss value of 10 to 45 as measured by the method described in JIS Z8741:1997.

2. 2. The packaging material according to claim 1, wherein the surface protective layer has a 60 degree gloss value of 10 to 35 as measured by the method described in JIS Z8741:1997.

3. 3. The packaging material according to claim 1, wherein the heat seal layer has a thickness of 1 to 10 μm.

4. The average basis weight of the paper base material is 50 to 300 g / m 2 The packaging material according to claim 1 or 2,

5. 3. The packaging material according to claim 1, wherein the heat seal layer comprises at least one resin selected from the group consisting of an ethylene-vinyl acetate copolymer resin, an acrylic resin (D), and an ethylene-based ionomer.

6. A packaging bag formed from the packaging material according to claim 1 or 2.

7. A method for producing a packaging material having a heat seal layer, a barrier layer, a paper base material, a printing layer, and a surface protective layer, comprising the steps of: A step 1 of forming the printing layer by flexographically printing a printing ink containing a styrene-acrylic copolymer resin (B) and / or a styrene-maleic acid copolymer resin on one surface of the substrate containing the paper substrate; A step 2 of forming the surface protective layer having a 60 degree gloss value of 10 to 45 as measured by the method described in JIS Z8741:1997 by flexographically printing an overcoat agent containing a styrene-acrylic copolymer resin (A) on the printed layer; Step 3 of applying a heat seal agent to the other surface of the base material including the paper base material to form the heat seal layer; and step 4 of forming the barrier layer, the barrier layer comprising at least one selected from the group consisting of a polyvinyl alcohol-based resin, a styrene-based resin (C), an acrylic-based resin (D'), aluminum, and an inorganic oxide, on the substrate comprising the paper substrate.

Citation Information

Patent Citations

  • Coating material and its method for production, and decorative paper

    JP2001192617A

  • Laminated film

    JP2004142238A

  • Gas barrier laminated film

    JP2007136984A

  • Aqueous pigment dispersion and aqueous printing ink composition comprising the same

    JP2011122023A

  • Water-based gravure printing ink composition for carton

    JP2013035967A